Conventional and Organic Wheat Germ Have Distinct Physiological Effects in the Tobacco Hornworm, Manduca Sexta: Use of Black Mutant Assay to Detect Environmental Juvenoid Activity of Insect Growth Regulators - Ffrench, Jivonsha; Tracewell, Jaime; Suzuki, Yuichiro (Frontiers in Insect Science, 2021)
Stored grains used in artificial diets are often treated with insecticides to control infestation by pests. In recent years, insect growth regulators (IGRs) have become an increasingly popular form of insect pest control in agricultural settings. Most IGRs specifically target insects by either disrupting their endocrine system or their chitin synthesis. One type of IGRs comprises of chemical analogs of juvenile hormone (JH), a major hormone involved in growth and development of insects. Here we demonstrate that conventional wheat germ contains JH activity and impacts growth and development of the tobacco hornworm, Manduca sexta. Feeding diet containing conventional wheat germ delayed the timing of metamorphosis in wildtype larvae by extending the duration of the final instar. Diet with conventional wheat germ also inhibited melanization of the black mutant larvae and induced the expression of the JH response gene, Krüppel homolog 1. We demonstrate that the black mutant bioassay is a sensitive assay that can determine the amount of JH activity in stored grains and suggest that this assay may offer a quick and reliable assay to determine the amount of environmental juvenoids. Researchers are urged to use caution when purchasing stored grains for mass-rearing of research insects.